polarities, limits and thresholds - Rainha, Ana; Varzim Miranda, Marta; Azevedo, Margarida; Lemos, João (Design/Arts/Culture, 2025)
polarities, limits and thresholds The present time is played out in insoluble conflict and the end of any debate is all or nothing, has shown polarisation to be a figure of our times. In effect, there is a set of technological, political and cultural conditions that determines the constant extremism of positions and transforms everything and everyone into antagonists. The excessive polarisation of society has instrumentalised causes, radically compromising the complexity of the world and the possibility of a common place. But, in contrast, it has also given new visibility to identity issues and collaborative approaches, allowing for a better understanding of differences and the widening of frames of reference. By placing these discourses as central issues, the use of tensions without constraints between antagonistic poles transposes protocolary categories and challenges assumptions of knowledge, questions aesthetic and cognitive criteria, highlights limits and unfolds practices. The terms that make them up show a new consistency in collaborative approaches and have fuelled new directions for research and education, such as the goals for the United Nations’ 2030 Agenda. Thus, the “decolonial” movements have emphasised distinct visions in the understanding of history and have constituted more corporeal narratives; the “relational” modes of constitution have mobilised proximity politics, favouring the purpose of an assembly and the continuous exercise of negotiation; and the “speculative” exercises have revealed possibilities of coexistence, finding value in unexpected connections. We may say that the challenge lies in knowing how to maintain this availability, how to continue this dialogue and generate a difference in action, how to notice these particular ideas and experiences, that is, how to live up to the emerging vitality. Guided by the terms proposed in the title of the publication – Polarities, Limit and Threshold – the articles present readings of a more theoretical and speculative nature. From the perspective of authors who are fundamental to understanding the topic, some models, approaches and technologies from the social and human sciences disciplinary field are explored. This seems to constitute new research terminologies in art and design courses and bring academia closer to the contexts surrounding it. Exercises carried out with students – from different schools and education levels – are framed in different pedagogical projects. Narrative or disciplinary limits are considered in these cases, while mediation practices and devices are perceived as potential agents in redefining this initial limit condition. The political and visual rhetoric, the autonomy of individual subjectivity, and the circulation of images and texts – as well as the emancipation of the tools and processes determining it – configure more particular approaches, resonate experiences, bodies and places, and explore other forms of existence in art and design. ANA RAINHA